Re-Membering Hospitality in the Mediterranean
XV, 281 p. 3 illus., 1 illus. in color.
Keywords: Re-Membering Hospitality in the Mediterranean examines the embodied praxis of hospitality—whether through the ritual modes of religious history, the pages of literature, the visual arts, dystopian narratives of the future, or the realpolitik of shelter and asylum. It moves beyond dominant transit tropes of aporetic exchange (in the lineage of Jacques Derrida). The volume offers a fractal view of Mediterranean studies as inflected by the lived, aesthetic, and philosophical histories of hospitality. This book brings together leading voices ranging from early-career to established scholars across the social sciences and the humanities to argue for a distinct focus on the Mediterranean pre/conditions and pre/histories of hospitality. To date, there has been no interdisciplinary intervention that takes up hospitality as a starting point to critical thinking about Mediterranean studies as an expansive, dynamic, and ever-evolving discipline. Against the inescapable backdrop of necropolitics and catastrophe, Re-Membering Hospitality in the Mediterranean offers a rich, agentive alternative for Mediterranean worldmaking. yasser elhariry is Associate Professor of French at Dartmouth College. He is the author of Pacifist Invasions: Arabic, Translation, and the Postfrancophone Lyric, and co-editor of Literature as Sound Studies. Isabelle Keller-Privat is Professor of English at the University Toulouse Jean Jaurès. She is chief editor of Caliban, French Journal of English Studies, and has co-edited various collections of interdisciplinary papers on exile and migration, travel letters, and Mediterranean criticism. Her current research focuses on travel literature and poetry and on the ethics and praxis of hospitality in Anglophone literature. Edwige Tamalet Talbayev is Associate Professor of French at Tulane University and Professor Extraordinarius at the University of South Africa. She is the author of The Transcontinental Maghreb: Francophone Literature across the Mediterranean, and co-editor of several volumes, among them Critically Mediterranean: Temporalities, Aesthetics, and Deployments of a Sea in Crisis and Water Logics (forthcoming). Her current research draws on biotheory, new materialism, and ecocriticism to theorize the drowning of migrants attempting to cross the Mediterranean. She is Editor of the journal Expressions maghrébines and a co-Editor of the Passagen book series with Georg Olms Verlag.